A modest proposal for Europe: a two-part plan for overcoming the eurozone's crisis, redesigning its crumbling architecture, and reinvigorating the European Project. (1st January 2011) - Varoufakis, Yanis; Holland, Stuart
During 2010, each and every response by the Eurozone to the galloping sovereign debt crisis has been consistently underwhelming. Monthly European Union Summit pronouncements, which during the first half of 2010 were met with initial goodwill by the markets and commentators, quickly proved the harbinger of further deepening of the crisis. By the end of 2010, the markets did not even wait for the European Union's leaders to conclude their monthly meetings before signalling another jump in yields and a further deterioration of the continent's financial outlook. Eventually, it became clear to everyone that the European approach (of extending expensive loans to fiscally stricken sovereigns on condition of savage austerity) was deeply flawed. This article outlines the basis of a policy mix that would end the crisis without any substantial institutional changes. It is in this particular sense that this proposal is both practical and modest.